Assessment of zygosity and nitrogen used efficacy in Mekongga transgenic rice - MACHZANI QURAITUL AINI; SUHARSONO SUHARSONO; ANIVERSARI APRIANA; ATMITRI SISHARMINI; TRI JOKO SANTOSO; KURNIAWAN RUDI TRIJATMIKO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Aini MQ, Suharsono, Apriana A, Sisharmini A, Santoso TJ, Trijatmiko KR. 2022. Assessment of zygosity and nitrogen used efficacy in Mekongga transgenic rice. Biodiversitas 23: 4040-4046. Nitrogen (N) is a vital macronutrient that can be a limiting factor for rice plant growth. Nitrogen-efficient plants can be assembled by modifying nitrogen-related metabolic pathways to improve Nitrogen Use Efficiency (NUE) in plants. T0 generation of transgenic Mekongga rice plants containing the LeAlaAT gene was obtained. In transgenic plant research, zygosity test was desirable to ensure the integration and inheritance stability of transgene. This study aimed to assess zygosity and nitrogen use efficacy of two transgenic Mekongga rice lines, namely M41 and M50. This research involved three main activities, i.e. detection of flanking sequence for T0 generation by TAIL-PCR method, zygosity test for T1 generation, and efficacy test for T2 generation of Mekongga transgenic lines in response to different N fertilizer rates of 0, 60, 90, and 120 kg ha?1. Zygosity analysis showed that six out of 14 M41 and three of 13 M50 transgenic lines were homozygous for LeAlaAT transgene. The efficacy test showed that homozygous transgenic lines had higher tiller numbers, grain numbers, and biomass compared to non-transgenic ones under the same nitrogen level. The notable discrepancies of the transgenic plants can also be recognized in the absorption, agronomical, and grain NUE of the studied plants.